THE ROLE OF ACUPUNCTURE IN OVERCOMING COMPLAINTS OF CARPAL TUNNEL SYNDROME - Dela Ramona; Indri Seta Septadina (International Islamic Medicine Forum, 2026)
Carpal Tunnel Syndrome (CTS) is a condition characterized by damage to the peripheral nervous system, causing pain, numbness, and hand weakness. Despite various treatments, neurological disorders remain a significant therapeutic challenge. The therapeutic effects of acupuncture are attributed to several mechanisms, including pain modulation related to endorphin release and gate control theory, increased blood flow, reduced inflammation, and electrophysiological effects. These mechanisms collectively contribute to reducing symptoms associated with carpal tunnel syndrome. Evidence suggests that acupuncture is beneficial in treating CTS. Research has shown that acupuncture can improve nerve conduction study parameters in sensory and motor nerves, reduce pain, and improve overall nerve function. Although more rigorous research is needed to characterize the effects of acupuncture on carpal tunnel syndrome fully, existing evidence supports its use as a complementary therapy. Standardized acupuncture protocols that combine physiological correlation with peripheral nerves and traditional approaches to pain management appear to be effective. Further studies with larger sample sizes and randomized comparisons of sham acupuncture will help establish acupuncture as a guideline for treating CTS conditions. This review explains the potential of acupuncture as a complementary therapy in treating complaints in the condition of carpal tunnel syndrome.